Turning a blind eye? Compliance to minimum wages and employment - Andrea Garnero; Claudio Lucifora (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
In this paper, we explore the relationship between non-compliance with bargained minimum wages and employment. We illustrate the role of labour courts with respect to the Constitutional provision of "fair" wage and sketch a model in which firms choose their desired levels of employment and non-compliance. We show that when employers internalize the expected costs of non-compliance, the effect of deviating from the bargained minimum wages on employment levels are modest, or null. Using data from the Italian LFS, we find evidence of a positive, but small, trade-off between non-compliance and employment. We discuss the policy implications of these findings for wage bargaining, also considering the costs that "turning a blind eye" to non-compliance implies for the Italian system of industrial relations.
Keywords: J08; J31; J52; J83; 330; Collective bargaining; sectoral minimum wages; compliance